Qualitative Analysis of standard Amino acid by Thin Layer Chromatography in examination of Inborn Errors of Metabolism - Hussein, Muna A.; Hameed, Rana M.; Hnewa, Riyadh A.-A. (Scientific Journal of Medical Research, 2021)
Metabolism is divided into various pathways in which constituents are converted by enzymes that catalyze the transformation of the substrates (synthesis or degradation). Metabolic problems can occur when one or more of these enzymes are not functioning properly (i.e., high or low levels) or are absent. Most IEMs are inherited in an autosomal recessive (AR) manner. The overall rate of inborn metabolic errors is estimated to be between 1:800 and 1:1000 live births, while the frequency is likely substantially higher due to clinical diagnosis challenges and diagnostic testing constraints. Incidence and prevalence of IEM differed between countries. Particular abnormalities of amino acid metabolism, disorders of carbohydrate metabolism, disorders of lipid metabolism, and disorders in the metabolism of purines and pyrimidines are all classified depending on the impaired metabolic pathway or enzymes involved in the generation of hazardous chemicals .aims or objectives in the study was to introduce a separation method of standard amino acid that could be effective for the detection amino acid disorder by producing distinguishable strategies based on silica gel TLC plates. Methods: The present work included a case-control study. Samples were selected from the patients attending the rare diseases unit, AL-children teaching hospital, Karbala. Blood and urine samples were collected from the volunteers, participants had no history of IEM, and the standardization of 20 amino acid was done by TLC (10 times for each amino acid). After that, the separation of amino acid in the serum and urine was performed for the patient and control group. Results: The study was includes 56 patients with age ranging from 7 days to 15 years. Infants of age less than 1month were 7 (12%), newborn aged from 2 to 12 months numbered 39 (69%) and children aged greater than 1year were 10 (17%), females was 22 (39%) and males represented 34 (60%), our study show that 41% of the suspected IEM patients were with a sign of jaundice, and 18, 5, 16, 29, 5, and 32% with diarrhea, dehydration, acidosis, vomiting, hepatomegaly, and flatulence respectively. Results were shown about 39%, 18%, 41%, 50%, 36% of suspected IEM patients were with Intellectual delay, Lethargy, Spasticity, Hypotonia, Epileptic seizures, respectively. Standardization of amino acids TLC was performed based on different strategies: the study results were established different strategies shown good demonstration of the standard AA throughout the retention factor (Rf) (mean and /or range), the arithmetic retention factor was result in subdivided of AA into 6 groups accordingly. Also, the standardization of AA were separated based on producing various distinguishable colors/ shapes. The above three methods were help to identify amino acid in the serum and urine samples. Conclusion: This study was concluded that thin layer chromatography (TLC) was an easy qualitative method, convenient and inexpensive way that could use to determine types of components (AA) were in a mixture of a suspected IEM patients